Keadilan Restoratif Sebagai Alternatif Dalam Penyelesaian Pelanggaran Tata Ruang - Hensi Novelly Irwan; Sukirno Sukirno (Notarius, 2023)
AbstractSpatial planning problems are closely related to urban development and development that exploits the widest possible space for economic factors, but ignores environmental functions. This research aims to provide conceptual ideas for resolving violations restorative justice approach. This research uses normative juridical. The collection technique uses literature study, then analysed using qualitative data analysis method. The result research is a law enforcement mechanism in the field of spatial planning for criminal offences can begin after the ultimum remedium principle is applied. Spatial law enforcement for the settlement of criminal offences of imprisonment and fines is not appropriate so that case settlement is needed by prioritising restoration actions to restore the function of space according to the RTR as a form of awareness and responsibility of the perpetrator.Keywords: restorative justice; spatial planning; offenseAbstrakPermasalahan penataan ruang erat kaitannya dengan perkembangan perkotaan dan pembangunan yang mengeksploitasi ruang seluas-luasnya demi faktor ekonomi, tetapi mengabaikan fungsi lingkungan. Penelitian ini bertujuan untuk memberikan gagasan konseptual bagi penyelesaian pelanggaran dengan pendekatan keadilan restoratif. Penelitian ini menggunakan yuridis normatif. Teknik pengumpulan menggunakan studi kepustakaan, kemudian dianalisis menggunakan metode analisis data kualitatif. Hasil penelitian adalah mekanisme penegakan hukum pada bidang tata ruang untuk tindak pidana dapat dimulai setelah prinsip ultimum remedium diterapkan. Penegakan hukum tata ruang untuk penyelesaian perkara tindak pidana kurungan penjara dan denda tidak tepat sehingga diperlukan penyelesaian perkara dengan mengedepankan aksi-aksi restorasi pemulihan fungsi ruang sesuai RTR sebagai bentuk keinsyafan dan tanggung jawab pelaku.Kata kunci: keadilan restoratif; tata ruang; pelanggaran